LIBERALISME GOLONGAN INKARUSSUNNAH DI INDONESIA DAN MALAYSIA - Sulidar Sulidar (State Islamic University North Sumatra, 2010)
Abstract: Liberalism of Anti-Prophetic Tradition in Indonesia and Malaysia. Liberalism thought which is pursuant to free understanding in comprehending nas the syariat of non solely one branch of habit thought supported by people of Islam in this world specially in Indonesia and Malaysia. Liberalism thought supported by this Moslem people in fact form the system of aqidah is which finally concluding of conception and religious service ‘separate’. The perpective Study of Hadith, inkarussunnah basically support the liberalism thought which in fact ‘ trussed’ with the free understanding in comprehending nas of the syariat especially from text of Hadith of Prophet. This article will elaborate the aspect of liberalism of faction inkarussunnah trod in Indonesia and Malaysia and its bearing with the past history forming liberalism rationale. This article will become the theory base in liberalism thought in inkarussunnah focusing to field study especially in Indonesia and Malaysia. Kata Kunci: liberalisme, inkarussunnah, hadis